Perfectionism and beliefs about emotions in adolescents with Chronic Fatigue Syndrome and their parents: A Preliminary Investigation in a Case Control Study nested within a cohort - Loades, M.E. (Psychol Health, 2019)
OBJECTIVES: To investigate perfectionism and beliefs about emotions in adolescents with Chronic Fatigue Syndrome (CFS) and their parents. DESIGN: Case-control comparing adolescents (age 11-18) with CFS (N = 121), asthma (N = 27) and healthy controls (N = 78) with a 3 month follow up for CFS participants. MAIN OUTCOME MEASURES: Adolescents: Chalder Fatigue Questionnaire, physical functioning, Beliefs about Emotions scale (BES), Child and Adolescent Perfectionism Scale, Frost Multidimensional Perfectionism Scale (FMPS). Parents: BES, FMPS, Self—sacrificing scale, Affective styles questionnaire. RESULTS: Adolescents with CFS did not consistently report higher levels of perfectionism and unhelpful beliefs about emotions than adolescents with asthma or healthy adolescents. Mothers’ and adolescents’ beliefs about emotions and unhelpful perfectionism were significantly associated (p = .007). Linear regression found that neither adolescent perfectionism nor beliefs about emotions accounted for variance in subsequent fatigue or physical functioning. CONCLUSION: Parental perfectionism and emotion regulation style may contribute to perfectionism in adolescents with CFS. Parental representations could contribute to fatigue maintenance.